Border crossing design in light of the ASEAN Economic Community: Simulation based approach - Sathaporn Opasanon (2018)
© 2016 Elsevier Ltd. Customs post is a logistics infrastructure playing a critical role in international transportation. This research provides a systematic framework and simulation analysis for designing operations and infrastructure for modern customs and cross-border transport. A case study of the largest customs post of Thailand in terms of cargo traffic, is carried out to portray the procedural steps of the proposed approach. Literature review and in-depth interviews with associated control agencies were conducted to identify required infrastructure components, border clearance procedures and customs formality in light of the ASEAN Economic Community. Linear regression models were developed to predict the future annual volume of traveler and vehicle flow. Simulation models were constructed to justify various operations and designs of key border-crossing facilities, including immigration control booths, vehicle inspection station and truck clearance area. The principles of transport and trade facilitation were adopted to ensure the effectiveness and efficiency of border crossing process. The results suggest that split configuration with joint inspections on both sides is the most practicable border control for the customs post where joint customs inspection is performed in the country of entry. To avoid unnecessary traffic interruption by different types of traffic, passenger and freight flow are separated in the design. For personal vehicles, a drive-through border crossing is proposed to allow a driver to obtain immigration and customs checks via the vehicle inspection booths without getting off the car. The analytical framework and simulation analysis proposed in this research is practical and useful for analyzing the design of other customs posts with similar traffic and cross-border patterns.